Kebijakan Indonesia dalam Menghadapi Ancaman Ekonomi Maritim Akibat Proyek Reklamasi Singapura - Lukyana Nabillah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Indonesia has a very extensive land and water area. However, with this vast body of water, problems often arise. Because water areas are areas that are vulnerable to conflict. So the reclamation carried out by Singapore has had an impact on shifting the determination of maritime boundaries between Indonesia and Singapore. So this research uses qualitative research to explain and explain the issues. As well as using descriptive data that is adapted to the problem being studied. In this way, this research analyzes and shows the policies that Indonesia has implemented in responding to the reclamation issue that threatens the maritime economy. Such as diplomacy, agreements and security carried out by Indonesia to protect and prevent threats to the maritime economy in accordance with international law or UNCLOS 1982.